PENGATURAN PERTANGGUNGJAWABAN SWASTA DALAM KECELAKAAN BENDA ANGKASA - Dewi Enggriyeni (UNES Law Review, 2023)
Responsibility in space law is regulated in the 1967 Outer Space Treaty and the 1972 Liability Convention. These rules generally regulate the role and form of state responsibility in space activities that cause accidents. The current development of the legal space has begun to involve the private sector as the organizer of space activities, but so far regulations at the international and national levels have not regulated the roles and responsibilities of the private sector. To answer this problem, normative juridical research methods are used, namely legal research which bases the research results on secondary data, namely primary, secondary, and tertiary legal materials relating to personal responsibility in artificial space object accidents. From the research conducted, it can be concluded that the regulation of responsibility for space accidents that cause losses are borne by the state because the celestial bodies are registered in the name of the state, but in terms of payment of compensation incurred, it is borne by the state. space operator. The existing laws and regulations in Indonesia do not yet regulate the accountability mechanism for the private sector, because the Space Law only states that the private sector can play a role in space commercialization activities.